2017
DOI: 10.1186/s12958-017-0260-7
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3 promotes embryo attachment via up-regulation of leukemia inhibitory factor in vitro

Abstract: BackgroundA receptive endometrium is essential for maternal-embryonic molecular communication during implantation. However, the specific molecular regulatory mechanisms of the endometrial capacity remain poorly understood. Here, we examined activating transcription factor 3 (ATF3) expression in human endometria and the functional effect of ATF3 on embryo attachment in vitro.MethodsImmunohistochemistry (IHC) was used to assess the ATF3 expression patterns in human endometria. Quantitative real-time PCR (qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Several associated transcription factors reportedly participate in the preparation of human endometrial receptivity, such as homeobox containing transcription factor 10 (Hoxa10) 21 , signal transducer and activator of transcription 3 (STAT3) 22 , and activating transcription factor 3 (ATF3) 23 . Furthermore, LIF is considered to be a direct downstream target gene of ATF3 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several associated transcription factors reportedly participate in the preparation of human endometrial receptivity, such as homeobox containing transcription factor 10 (Hoxa10) 21 , signal transducer and activator of transcription 3 (STAT3) 22 , and activating transcription factor 3 (ATF3) 23 . Furthermore, LIF is considered to be a direct downstream target gene of ATF3 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Several associated transcription factors reportedly participate in the preparation of human endometrial receptivity, such as homeobox containing transcription factor 10 (Hoxa10) 21 , signal transducer and activator of transcription 3 (STAT3) 22 , and activating transcription factor 3 (ATF3) 23 . Furthermore, LIF is considered to be a direct downstream target gene of ATF3 23 . We have previously demonstrated that Krüppel-like factor 12 (KLF12) is expressed in the glandular epithelium (GE) and stromal cells of secretory-phase endometrial tissue and that KLF12 negatively regulates endometrial decidualization through the transcriptional repression of target genes both in vitro and in vivo 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that ATF3 was located in both human endometrial epithelial cells and stromal cells, and its expression was dysregulated in RIF patients. In epithelial cells, ATF3 could promote embryo adhesion in vitro by transcriptionally increasing LIF expression 32 . In this study, we focused on the stromal cells to investigate the function of ATF3 on decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 is induced by a variety of signals, including cell cycling, neutrophil migration and sexual differentiation [27][28][29]. Cheng et al revealed that ATF3 has an important role in regulating human endometrial receptivity and embryo attachment in vitro via up-regulation of leukemia inhibitory factor [30]. Those 461 genes were enriched in the biological processes of anion transmembrane transport, response to corticosteroid and response to glucocorticoid (P-value < 0.05).…”
Section: Functionally Important Regulatory Modules Are Identi Ed In Ementioning
confidence: 99%